Exploring the limits of social solidarity: welfare tourism and EU citizenship - Mantu, Sandra; Minderhoud, Paul (UNIO – EU Law Journal, 2016)
Political debates concerning the free movement of (poor) EU citizens (mainly from the newer EU Member States) have focused upon the twin issues of abuse of free movement rights and welfare tourism, despite the lack of meaningful evidence that the two are actually taking place on a wide scale in the EU. This article discusses the increasing political contestation of EU mobility as captured by notions such as, welfare tourism and poverty migration. The analysis of the case law of the Court of Justice of the European Union on issues of social rights and EU citizenship shows a noticeable shift towards stricter interpretations of the scope of social solidarity for mobile EU citizens. We argue that the coupling of these two aspects of EU mobility raises questions about the scope of EU citizenship and its nature as a fundamental status.